Spatial charateristics of public interior spaces that addres the needs and preferences od selected LGBTQIA+ individuals - Dandan, Frances maria P.; Queveo, Ma. Teresa (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Queer spaces emerged as places of refuge, comfort, and protest for the LGBTQIA+ community. Due to rampant discrimination, systemic oppression, and normative traditions, most public spaces are not inclusive or accommodating to the queer community. The purpose of this study is to discover the spatial characteristics of public interior spaces that will address the needs and preferences of the LGBTQIA+ with the goal of developing recommendations that interior designers can use in future projects. An exploratory qualitative research was applied where ten LGBTQIA+ individuals were selected through purposive and snowball sampling approaches. Semi-structured interviews were conducted both online and face-to-face depending on the participants’ availability. Data was analyzed through thematic analysis. Findings showed that the aspects of public interior spaces that address participants’ needs are manifested through options for private and personal spaces, social spaces, and accessible and equal spaces. In terms of spatial characteristics that address participants’ preferences, it was found that they prefer spaces that have good natural lighting, views of the outside, and comfortable seating. There are negative feelings towards dark spaces, bland colors, overexposed spaces, and lack of proper furniture. Overall, the qualities of spaces that can be recommended as bases for designing spaces that include and represent the LGBTQIA+ are symbolic, nonconforming, nonbinary, inclusive-accessible, and inclusive-relational, and comfortable and home-like (with desired preferences for neutral and pastel colors, wood and reflective finishes, comfortable, laid-back, curvy and round furniture, and bright warm lighting).
Thesis
Includes bibliographical references (pages 102-113)
Keywords: Interior decoration -- Philippines; Public spaces -- Philippines; Sexual minorities -- Philippines